Biallelic loss of CDKN2A is associated with poor response to treatment in pediatric acute lymphoblastic leukemia. Issue 5 (4th May 2017) - Braun, Marcin; Pastorczak, Agata; Fendler, Wojciech; Madzio, Joanna; Tomasik, Bartlomiej; Taha, Joanna; Bielska, Marta; Sedek, Lukasz; Szczepanski, Tomasz; Matysiak, Michal; Derwich, Katarzyna; Lejman, Monika; et al.
Abstract: The inactivation of tumor suppressor genes located within 9p21 locus ( CDKN2A, CDKN2B ) occurs in up to 30% of children with B-cell precursor acute lymphoblastic leukemia (BCP-ALL), but its independent prognostic significance remains controversial. In order to investigate the prognostic impact of deletions and promoter methylation within 9p21, 641 children with newly diagnosed BCP-ALL using methylation specific multiplex ligation-dependent probe amplification (MS-MLPA) were investigated. A total of 169 (26.4%) microdeletions in 9p21 were detected, of which 71 were homozygous. Patients with CDKN2A homozygous deletions were older at diagnosis ( p  < .001), more frequently steroid resistant ( p  = .049), had higher WBC count ( p  < .001), higher MRD at Day 15 ( p  = .013) and lower relapse-free survival [ p  = .028, hazard ratio: 2.28 (95% confidence interval: 1.09–4.76)] than patients without these alterations. CDKN2A homozygous deletions coexisted with IKZF1 and PAX5 deletions ( p  < .001). In conclusion, CDKN2A homozygous deletions, but not promoter methylation, are associated with poor response to treatment and increased relapse risk of pediatric BCP-ALL.